Analysis of Factors Influencing the Implementation of an Integrated Referral System (SISRUTE) in an Effort to Improve the Quality of Health Service Facilities - Sutrisnawati, Ni Nyoman Dwi; Suandari, Putu Vierda Lya (Indonesian Journal of Global Health Research, 2023)
The Integrated Referral Information System (SISRUTE) is an application designed and implemented nationally since 2016 which helps the referral process effectively and efficiently by providing referral information for individual health services. SISRUTE has been used by Community Health Centers as First Level Health Facilities (FKTP) and Hospitals (Advanced Care Health Facilities). This research aims to analyze the factors that influence the implementation of SISRUTE in Indonesia, both at the FKTP and FKRTL levels in Indonesia. The research method used is a systematic review, complemented by secondary data search using the PRISMA method to analyze the influencing factors in the process of implementing the integrated referral system in Indonesia. The results obtained show that the application of SISRUTE is influenced by several factors including data quality, human resources and organization, facilities, budget allocation, policies, system quality, communication and reporting and evaluation monitoring. In general, the most influential factors are data quality, infrastructure, policies and standard operational procedures, data management processes and human resources both in terms of training or appointing a team specifically for handling SISRUTE. There is a need for commitment from the leadership of FKTP and FKTRL to be able to encourage improvements in infrastructure both in terms of hardware, software and internet networks as well as technical assurance regarding human resources who are responsible for operating the system.